Should Renaturalised and Recultivated Landscapes Appear in Landscape Typology? - Luc, Małgorzata; Szmańda, Jacek (Quaestiones Geographicae, 2014)
Landscapes constantly change under the influence of natural and anthropogenic factors. They can be destructive as well as leading to regeneration of landscapes which have been imbalanced. When this process occurs in a natural or human-controlled manner with the use of natural elements of the environment, it is called renaturalisation, and the resulting landscape - renaturalised landscape. Where landscape restitution occurs under the purposeful, sustainable and rational human influence, we talk of the recultivation process and the resulting landscape is termed recultivated. Examples of both of these terms added to landscape classification have been described based on several quarries existing within the City of Krakow.